Subjective and objective limits of tapping in criminal proceedings - Kluza, Jan (Ius Novum, 2019)
The article presents the latest extraordinary appeal measure against the final judicial decisions that was provided for in the Supreme Court Act. The analysis of the grounds for this extraordinary appeal and of the procedure before the Supreme Court proves that this solution is of a cosmetic nature and will not bring about the desired changes in the system of justice.